Draft genome sequence of Leptospira interrogans serovar Bataviae strain LepIMR 22 isolated from a rodent in Johor, Malaysia - Amran, F.; Khalid, M.K.N.M.; Mohamad, S.B.; Ripen, A.M.; Ahmad, N.; Goris, M.G.A.; Muhammad, A.H.; Halim, N.A.N. (American Society for Microbiology, 2016)
Leptospira interrogans serovar Bataviae was recently identified as one of the persistent Leptospira serovars in Malaysia. Here, we report the draft genome sequence of the L. interrogans serovar Bataviae strain LepIMR 22 isolated from kidney of a rodent in Johor, Malaysia.